2024
DOI: 10.3389/fenvs.2023.1327260
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of nitrogen and phosphorus contents in soil and water in an agricultural catchment of the three Gorges reservoir area

Chenglong Chen,
Hua Deng,
Guixin Xin
et al.

Abstract: To explore the impact of different land use modes on the contents of nitrogen and phosphorus in soil and water in the agricultural basin of the Three Gorges Reservoir, the differences in the nitrogen and phosphorus contents in soil and shallow groundwater under different land use modes were studied by using sample data collected in the field. The typical agricultural small watershed at the heart of the reservoir area was selected as the research object. The differences in the nitrogen and phosphorus loss conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…N is highly mobile and can be easily transported by both pathways. Interflow has been reported as the predominant pathway for NO 3 − -N loss from sloping farmland (Jia et al, 2007), although conflicting results have been obtained in other studies (Chen et al, 2024). In this study, TDN was identified as the primary form of N loss from sloping farmland.…”
Section: Effect Of Rb-prb With Vfs On Nitrogen Loss From Sloping Farm...mentioning
confidence: 61%
“…N is highly mobile and can be easily transported by both pathways. Interflow has been reported as the predominant pathway for NO 3 − -N loss from sloping farmland (Jia et al, 2007), although conflicting results have been obtained in other studies (Chen et al, 2024). In this study, TDN was identified as the primary form of N loss from sloping farmland.…”
Section: Effect Of Rb-prb With Vfs On Nitrogen Loss From Sloping Farm...mentioning
confidence: 61%